Performance Evaluation of Machine Learning Algorithms in Aspect-Based Sentiment Analysis on E-Commerce User Reviews - Maharani Pakpahan, Mira; Halmi Dar, Muhammad; Nirmala Sari Hasibuan, Mila (Publisher Cv. Inara, 2025)
The rapid growth of the e-commerce industry in Indonesia has resulted in a significant surge in the number of user reviews available on various digital platforms. These reviews contain valuable information about customer experiences related to price, product quality, service, delivery, and applications. However, the massive volume of data and its unstructured nature pose challenges in extracting relevant information. Aspect-Based Sentiment Analysis (ABSA) presents an approach that can provide deeper insights by identifying sentiment towards specific aspects within a review, rather than just the overall general sentiment. This study aims to evaluate the performance of several machine learning algorithms, namely Naïve Bayes, Support Vector Machine (SVM), Random Forest, and K-Nearest Neighbors (KNN), in implementing ABSA on e-commerce user reviews in Indonesia. The dataset used consists of 20,000 user reviews of the Shopee and Tokopedia applications obtained through a crawling process on the Google Play Store. The data is processed through several stages: text preprocessing, aspect and sentiment annotation, model training, and performance evaluation using accuracy, precision, recall, and F1-Score metrics. The evaluation results showed differences in performance among the tested algorithms. Naïve Bayes achieved an accuracy of 82.5%, KNN achieved 84.6%, Random Forest 87.1%, while SVM provided the best performance with an accuracy of 89.3% and an F1-Score of 88.3%. This difference in performance indicates that algorithms that are better able to handle high-dimensional text representations, such as SVM, are superior in aspect-based sentiment classification compared to other methods. Thus, this study not only provides a comprehensive overview of the effectiveness of machine learning algorithms in sentiment analysis in the e-commerce sector but also provides a practical basis for developing recommendation systems, improving customer service, and enhancing user experience strategies on digital platforms. This research is expected to serve as a reference in the application of machine learning to support the growth of the e-commerce industry in Indonesia.